Equitable Total Coloring of Spider Graph - K. Kalaiyarasan; D. Senthil Kumar (Utilitas Mathematica, 2025)
An equitable total coloring ( et )of a graph was introduced by Fu[4] in 1994. He gave the Conjecture that For any simple graph G satisfies condition 2 ) ( +G et  . The graph G (V,E) is called equitably Total k – Colorable if the vertex set and edge set of the graph can be partitioned into k non empty independent sets k T ,T ,T ,...,T 1 2 3 such that − 1 i j T T for every i and j. If the connected graph G is neither a complete graph nor an odd cycle then it satisfies the Equitable Coloring Conjecture. In this paper We examine and establish equitable total coloring of Spider Graph.